Biological Studies of Chalcogenolato-Bridged Dinuclear Half-Sandwich Complexes - Johnpeter, Justin P.; Gupta, Gajendra; Kumar, Jerald Mahesh; Srinivas, Gunda; Nagesh, Narayana; Therrien, Bruno (My University, 2013)
Cationic chalcogenolato-bridged diruthenium complexes [(?6-p-MeC6H4Pri)2Ru2(?-EC6H5)3]+ (E = S, 1; E = Se, 2; E = Te, 3) were obtained in EtOH from the reaction of (?6-p-MeC6H4Pri)2Ru2(?-Cl)2Cl2 with benzenethiol, benzeneselenol, and Na tellurophenolate, resp. The thiolato and selenolato derivs. are isolated in good yield as the chloride salts, while the tellurolato analog is isolated as the hexafluorophosphate salt. Similarly, the dinuclear pentamethylcyclopentadienyl (C5Me5) Rh and Ir complexes (?5-C5Me5)2M2(?-Cl)2Cl2 react with benzenethiol, benzeneselenol, and Na tellurophenolate in EtOH to give the corresponding cationic dinuclear complexes [(?5-C5Me5)2M2(?-EC6H5)3]+ (M = Rh, E = S, 4; E = Se, 5; E = Te, 6; M = Ir, E = S, 7; E = Se, 8; E = Te, 9). Cationic dinuclear complexes with mixed thiolato-selenolato and thiolato-tellurolato bridges were prepd., [(?6-p-MeC6H4Pri)2Ru2(?-EC6H5)(?-SCH2C6H4-p-But)2]+ (E = Se, 10; E = Te, 11) and [(?5-C5Me5)2M2(?-EC6H5)(?-SCH2C6H5)2]+ (M = Rh, E = Se, 12; E = Te, 13; M = Ir, E = Se, 14; E = Te, 15), starting from the neutral dinuclear complexes (?6-p-MeC6H4Pri)2Ru2Cl2(?-SCH2C6H4-p-But)2 and (?5-C5Me5)2M2Cl2(?-SCH2C6H5)2. All complexes are highly cytotoxic showing activity in the submicromolar range. The nature of the chalcogenolato bridges seems to have an impact on the activity, while the nature of the metal center plays a minor role. Among the complexes tested, the dinuclear complexes 1, 4, and 7 with the thiolato bridges show the highest activity on cancer cells and the best affinity for CT-DNA as demonstrated by cell biol. and biophys. expts. [on SciFinder(R)]
Keywords: chloro bridging dinuclear ruthenium sandwich reaction benzenethiol benzeneselenol tellurophenolate; dinuclear chloro bridging iridium sandwich reaction benzenethiol benzeneselenol tellurophenolate; chalcogenolato bridged dinuclear iridium ruthenium sandwich prepn anticancer agent; cytotoxicity chalcogenolato bridged dinuclear iridium ruthenium sandwich complex